Asuhan Keperawatan Gangguan Kebutuhan Dasar Nyeri Pada Ny.T Dengan Diagnosa Medis Ca Paru di Ruang Srikandi RS Wijaya Kusuma Purwokerto - Suseno Nino Nino; Sutrisno Sutrisno (Pena Medika Jurnal Kesehatan, 2023)
ABSTRACTLung cancer in a broad sense is all malignancy in the lung, including malignancy originating from the lung itself (primary) as well as malignancy from outside the lung (metastasis). In a clinical sense, what is meant by primary lung cancer is a malignant tumor originating from the bronchial epithelium (bronchial carcinoma) (Kemenkes RI., 2017). This case study aims to describe pain nursing care for a female patient Mrs. T with a diagnosis of Lung Ca in the Srikandi Room, Wijaya Kusuma Hospital, Purwokerto. Descriptive case study conducted from December 11 to December 14 2022 in the Srikandi Room, Wijaya Kusuma Hospital, Purwokerto with a patient population of 1 respondent. Data collection techniques used included: interviews, physical examination, observation, documentation study. After conducting an assessment of Mrs. T, it was found that a decrease in right-sided chest pain above the breast is one of the priority problems that often occurs in lung cancer patients. After taking nursing care measures, the reduction in chronic pain associated with tumor infiltration has been resolved.